2020
DOI: 10.1002/eat.23374
|View full text |Cite
|
Sign up to set email alerts
|

Eating disorders in times of the COVID‐19 pandemic—Results from an online survey of patients with anorexia nervosa

Abstract: Objective: The COVID-19 pandemic and the resulting public restrictions pose a psychological burden for humans worldwide and may be particularly detrimental for individuals with mental disorders. Therefore, the current study explored effects of the COVID-19 pandemic on eating disorder (ED) symptoms and other psychological aspects in former inpatients with anorexia nervosa (AN). Method: One-hundred and fifty-nine patients with AN-discharged from inpatient treatment in 2019-completed an online survey on contact h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
274
3
20

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 203 publications
(338 citation statements)
references
References 31 publications
(46 reference statements)
19
274
3
20
Order By: Relevance
“…The objective of this analysis was to characterize the impact of the COVID-19 pandemic on disordered eating behavior using inductive, thematic analysis of ED-related Reddit forums. Consistent with previous investigations [ 7 - 12 , 24 , 25 , 30 ], our findings indicate that the COVID-19 pandemic and associated public health prevention measures negatively impacted the psychiatric health of most users. Users frequently sought comfort in a time of heighted emotional distress by engaging in ED behavior, which was exacerbated by abrupt and involuntary changes in daily routine, exposure to food shortages and panic buying, closure of exercise facilities, and reduced access to care and social support networks.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The objective of this analysis was to characterize the impact of the COVID-19 pandemic on disordered eating behavior using inductive, thematic analysis of ED-related Reddit forums. Consistent with previous investigations [ 7 - 12 , 24 , 25 , 30 ], our findings indicate that the COVID-19 pandemic and associated public health prevention measures negatively impacted the psychiatric health of most users. Users frequently sought comfort in a time of heighted emotional distress by engaging in ED behavior, which was exacerbated by abrupt and involuntary changes in daily routine, exposure to food shortages and panic buying, closure of exercise facilities, and reduced access to care and social support networks.…”
Section: Discussionsupporting
confidence: 92%
“…Although some ED patients, particularly those in recovery, may modify social media accounts to turn attention to positive or recovery-focused content [ 7 ], those with untreated ED and those at risk for ED may be especially harmed by these media trends. Across existing studies, ED individuals consistently reported anxiety related to physical activity and the inability to exercise [ 9 - 11 , 24 ], especially after exposure to exercise-related media content [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, our qualitative analysis reflected that some participants were still able to identify and apply adaptive strategies in their lives: these included accessing social support, setting appropriate boundaries for self-care and protection, and adding adaptive strategies in the form of new structures and reinforcing activities, as implicitly aligned with behavioural activation approaches to depression [ 57 ]. Only two studies have examined the coping activities engaged in by people with EDs at this time: consistent with the importance of setting new structures and enjoyable activities highlighted by our participants, these previous studies found that among the most helpful activities for people with AN and BN were establishing routines, day planning and scheduling pleasant activities [ 12 , 13 ], in addition to time with family, yoga and gentle exercise.…”
Section: Discussionsupporting
confidence: 76%
“…The sudden societal changes and related stressors after the COVID-19 outbreak may also have worsened symptoms or have hindered the recovery of symptoms among individuals with existing mental health problems. In addition, the pandemic may have reduced access to or use of mental health care services, or forced mental health care workers to continue the treatment using online facilities instead of usual vis-à-vis contacts contributing to a deteriorating mental health [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%